Dampak Dominasi Teknologi Digital terhadap Pergeseran Nilai Kemanusiaan: Analisis Filosofis dalam Kehidupan Sosial Kontemporer - Raffa Shalsabila; Evy Nurmiati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
The dominance of digital technology in contemporary society has led to a shift in human values. Technology no longer serves merely as a tool but has evolved into a crucial system shaping interaction, communication, and behavior. This study uses qualitative methods to examine how digital technology influences human values in modern society. For this purpose, a literature review was carried out, incorporating thematic analysis of relevant sources. According to this study, the prevalence of digital technology has significantly transformed many aspects of social life. This includes the transition from a user-centered paradigm to a more automated system-centered paradigm; the conversion of human identity into data representation in digital systems; as well as the move from in-person to online communication within social exchanges. These effects undermine the quality of social relationships, reduce empathy and interpersonal interaction, increase dependence on technology, and lead to dehumanization. Furthermore, changes in information perception have the potential to improve digital literacy but simultaneously reduce the quality of critical public reflection. Nevertheless, digital technology continues to offer advantages such as easier access to information and productivity gains. Therefore, strategic efforts are needed to improve user-centered technology, digital skills, and adaptable regulations.